Long-memory in volatilities of German stock returns - Philipp Sibbertsen (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2001)
We show that there is strong evidence of long-range dependence in the volatilities of several German stock returns. This will be done by estimating the memory parameter of the absolute returns with classical log-periodogram regression as well as by employing the tapered periodogram. Both estimators give similar values for the memory parameter what indicates long-memory.
Keywords: 519; Long-memory; volatilities; log-periodogram estimation; Kapitalertrag; Börsenkurs; Volatilität; Schätztheorie; Deutschland